Simulation of storage system in data center - Goh, Wei Yang. (2012)
In recent years, data storage is one of the areas of computing that has evolved the most, and computer storage devices are now incredibly varied in terms of cost, performance, size and storage space. Each type of storage device has its own advantages, and to find that ideal solution involves the combination of the storage types. To study the complex behavior of how the storage devices handle the input/output requests of a computer system in the data center, a simulation system is use to aid with the studies in this project.